Larval development rates of Chrysomya rufifacies Macquart, 1842 (Diptera: Calliphoridae) within its native range in South-East Asia. (September 2016) - Yanmanee, Surasuk; Husemann, Martin; Benbow, Mark Eric; Suwannapong, Guntima
Graphical abstract: Highlights: ⿢ Chrysomya rufifacies represents an indicator species in forensic entomology. ⿢ We investigated the development of the species from the east of Thailand. ⿢ We present isomorphen and isomegalen diagrams for nine temperatures. ⿢ The lower threshold temperature for total development was 9.5 °C. Abstract: Chrysomya rufifacies represents an important indicator species in forensic entomology that is often used to estimate the minimum postmortem interval (PMImin ) in crime scene investigation. However, developmental rates differ locally, so that estimates should be based on regionally generated development data. Therefore, we determined the developmental rates of C. rufifacies within its native range in Thailand under nine constant temperature regimes: 15, 18, 21, 24, 27, 30, 33, 36 and 39 °C. Developmental times from egg to adult varied among the temperatures and were longest at 15 °C (618 h) and shortest at 33 °C (168 h). No pupae emerged at 39 °C. We used linear regression models to estimate the minimum development threshold temperatures for each life stage: egg stage = 9.5 °C, first to second instar = 10.8 °C, second to third instar = 11.5 °C, third instar to pupariation = 11.4 °C, pupariation to adults = 5.0 °C; the minimum threshold to complete all larvae stages was 11.1 °C and to complete all life stages from eggs to adult was 9.5 °C. We further generated isomorphen and isomegalen diagrams that can be used to quickly estimate the PMImin for forensic applications.